Hubungan Lama Menderita dan Indeks Massa Tubuh terhadap Gejala Neuropati pada Penderita Diabetes Melitus di Wilayah Kerja Puskesmas Kenali Besar - Hasyim Kadri; Nurfitriani Nurfitriani (Jurnal Akademika Baiturrahim Jambi, 2021)
Advances in technology have led to changes in lifestyle, such as the availability of various technological products that make it easier for human activities to become less mobile. Changes in behavior and eating patterns that lead to fast food with high energy, fat and low fiber content contribute greatly to the increase in the prevalence of diabetes mellitus. The purpose of this study was to determine the relationship between length of stay and body mass index on symptoms of neuropathy in patients with diabetes mellitus in the Working Area of the Kenali Besar Public Health Center, Jambi City. This research is a quantitative research with a cross sectional design. The population in this study were all people with diabetes mellitus in the Working Area of the Kenali Besar Health Center totaling 200 people, with a total sampling technique with a sample of 178 people. Data were obtained using a questionnaire. Statistical test using Chi-square test. The results showed that most of the respondents suffered from diabetes mellitus >5 years (83.7%), overweight (69.1%) and had symptoms of severe neuropathy (57.3%). There is a significant relationship between the duration of suffering from diabetes mellitus with symptoms of neuropathy with p-value = 0.012. There is a significant relationship between body mass index and symptoms of neuropathy in patients with diabetes mellitus with p-value = 0.022